PENERAPAN METODE CLOUD RECOGNITION PADA APLIKASI AUGMENTED REALITY PENGENALAN JENIS BUAH-BUAHAN - Septiana Ningtyas; Abdul Aziz Efendy (Institut Teknologi dan Bisnis Swadharma, 2021)
Augmented Reality is the merging of two-dimensional or three-dimensional virtual objects into a three-dimensional real environment. Then project these virtual objects in real-time. In the field of education, AR technology can be useful as a medium for student learning to be more attractive, more interactive, and imaginative whose objects are following the original. This study aims to produce fruit learning applications using Android-based Augmented Reality technology to support the learning process using the Multimedia Development Life Cycle (MDLC) method which consists of 6 stages, namely concept, design, material collecting, assembly, testing, and distribution. The result of the research is an augmented reality application for fruit recognition using a cloud recognition method based on C #, Unity 3D, and blender which applies marker based tracking method based on android which can be used as a learning tool for students.